Discovery of macrocyclic HDACs 1, 2, and 3 selective inhibitors for HIV latency reactivation. (1st September 2021) - Yu, Wensheng; Fells, James; Clausen, Dane; Liu, Jian; Klein, Daniel J.; Christine Chung, C.; Myers, Robert W.; Wu, Jin; Wu, Guoxin; Howell, Bonnie J.; Barnard, Richard J.O.; Kozlowski, Joseph
Graphical abstract: Abstract: A series of unique macrocyclic HDACs 1, 2, and 3 selective inhibitors were identified with good enzymatic activity and high selectivity over HDACs 6 and 8. These macrocyclic HDAC inhibitors used an ethyl ketone as the zinc-binding group. Compounds 25 and 26 stood out as leads due to their low double-digit nM EC50 s in the 2C4 cell-based HIV latency reactivation assay. The PK profiles of these macrocyclic HDAC inhibitors still needed improvement.